Assessment of method for buccal swab samples preservation in extreme environmental conditions for population genetics and forensic purposes. (December 2017) - Burgos, G.; Ormasa, D.; Camargo, M.; Iturralde, G.; Granda, JD.; Posada, Y.; Sanchez, M.; Tejera, E.; Calvopiña, M.
Abstract: The preservation of buccal swab samples in remote environments with high temperature and humidity is a huge problem in samples for forensic and population genetic samples. Since there are no low-cost methods that can generate good results, the action of TNE buffer has been evaluated. TNE buffer has the properties of inactivating nucleases, preventing the growth of microorganisms in the sample and maintaining the integrity of the cells under extreme environmental conditions. The advantage obtained with this poorly diffused method was that the swab does not required a drying process neither low temperatures prior to DNA extraction and analysis showing higher cell integrity and quality of DNA compared with controls.